Switching Behavior Nasabah Bank: Tinjauan Empiris Teori Keperilakuan Di Kota Makassar - Sri Rahayu Syah Rahayu Syah; Ibrahim Ibrahim; Sufardi Sufardi (Jurnal Ad'ministrare, 2018)
Public understanding of Islamic banking services is still low. The purpose of this study is to analyze the factors that influence the switching behavior of bank customers. This research method uses a quantitative approach and data collection using a questionnaire given to 200 bank customers who are taken on a non-probability sampling basis and analyzed using SPSS version 21. The results of hypothesis testing indicate that attitudes, subjective norms, perceived behavioral control, and system ease procedures have a positive and significant effect on the intention to switch bank customers, while social influences and effort expectancy do not affect the intention to switch bank customers. This research is relevant for management to design service products that provide convenience for users to increase the intention of users to transact with Islamic banks.